Equivalencia empírica y subdeterminación en las teorías físicas - Alejandro Cassini (Crítica)
The paper analyses two different senses in which it can be said that rival theories are empirically equivalent. This amounts to distinguish two types of underdetermination of theories by experience. The first is transient and relative to the status of scientific knowledge in one moment. The second is absolute and implies that no future experience will be able to confirm one theory and refute the others. That circumstance leads to conventionalism or skeptical relativism when the rival theories have empirical adequacy. Against this conclusion it is argued that we cannot know that two or more theories are empirically equivalent in the absolute sense. So, we have to assume that every example of underdetermination is merely transient. Evenin that case, it is possible to apply factual and non factual criteria of choice. If one theory cannot be selected by this way, further developments of both theories will be required. Finally, several cases of underdetermination in physical theories are discussed, and some strategies of assessment are proposed.